Lightning Activity Over Chilean Territory - Montana, Johny (2021)
This work presents the spatial distribution and temporal variability of lightning activity over the continental territory of Chile by means of Thunderstorms days (Td), on the basis of 7 years (2012–2018) of lightning measurement from World Wide Lightning Location Network (WWLLN). Td are obtained separately for the 15 geopolitical regions of Chile, reporting the higher lightning activity in the northeastern region of the country with 85 thunderstorms days per year. These values are mainly located in the mountains between 2,000 and 5,000 m.a.s.l. where extensive mining activity is located and there are electrical facilities of great importance for Chile. The Td values obtained in this study update the information presented by the World Meteorological Organization (WMO) in 1953, so far the only one available for the entire Chilean territory. From the diurnal cycle analysis, there is a marked mono-modal behavior of lightning activity in the afternoon for latitudes between (Formula presented.) S and (Formula presented.) S (regions XV, I, and II) and a different behavior of lightning activity over the region between (Formula presented.) S and (Formula presented.) S (regions X, XI, and XII) known as Chilean Patagonia, due to special weather conditions in that area. Further more, the seasonal analysis showed that the highest lightning activity occurs in January and February and the lowest activity takes place between June and August. Once again, the Chilean Patagonia showed a different behavior because the highest activity is presented in May and August, and the lowest in September. The analysis and results presented here contribute to the knowledge of lightning activity in the region that has not been characterized before and can serve as a basis for future research to determine the behavior of this natural phenomenon.